Model updating frameworks for the estimation of lateral soil-pile interaction parameters - Ioakim, Andreas (2025)
Resilient infrastructure systems, particularly in safety-critical applications such as offshore wind turbines (OWTs), demand advanced monitoring frameworks that can accommodate complex dynamics and inherent uncertainties. Structural Health Monitoring (SHM) is central to this goal, ensuring the operational integrity of OWT foundations while supporting safety, efficiency, and sustainability. This thesis advances the field of SHM by integrating physics-based modelling with data-driven techniques, combining the reliability of numerical simulations and the adaptability of data-oriented methods. This hybrid approach overcomes the limitations of purely data-driven methods, which can produce accurate but physically inconsistent predictions, and purely physics-based models, which can be computationally expensive and sensitive to parameter uncertainties.